KOMUNIKASI EFEKTIF DALAM PEMBELAJARAN USIA KANAK-KANAK PERSPEKTIF ISLAM - MS, Amiruddin (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
Islam as a hanif religion provides signs to communicate with children in the learning process. The formulation of this research problem is focused on effective communication efforts in the learning process for children according to Islamic perspectives. This research uses a qualitative approach with the literature study method. The results of this study indicate that effective communication that can be carried out in the learning process of childhood according to an Islamic perspective, are: 1) communicating with support / acceptance; 2) use the door opener; 3) listen attentively; 4) use the statement